Century 21 Computer Skills and Applications, Lessons 1-88, 11th Edition - Jack P. Hoggatt; Jon A. Shank (Cengage Learning, 2018)
Learn keyboarding skills that will prepare you for a lifetime of success with CENTURY 21 COMPUTER SKILLS AND APPLICATIONS. A complete family of proven solutions is included in this updated version, ready to help you face all the business challenges that will come your way. This useful text lets you tap into the latest keyboarding technology, helps you master computer applications using Microsoft Office 365/2016, and builds your communication skills. Important Notice: Media content referenced within the product description or the product text may not be available in the ebook version.